Evaluation of agronomic and fruit quality traits of miraculin transgenic tomato: Agronomic and fruit quality traits of miraculin transgenic tomato (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Carsono N, Desiana N, Nurrizqi FM, Elfakhriano IF, Anas, Sari S, Kusumiyati, Ohsawa R, Shimono A, Ezura H. 2022. Evaluation of agronomic and fruit quality traits of miraculin transgenic tomato. Biodiversitas 23: 2004-2009. Tomato cv. Moneymaker has been inserted with miraculin gene which can modify sour taste becomes sweet in the human tongue and, thus, it has potential as a sweetener. Evaluation of agronomic and fruit quality traits for this special transgenic tomato is a major concern that should be performed as substantial equivalence. The study's objective was to compare agronomic and fruit quality traits of transgenic miraculin tomato with those of its wild-type. The experiment employed a randomized block design, one genotype factor with two levels (transgenic vs. non-transgenic tomato cv. Moneymaker), and each was four replicates. Data were subjected to the Student t-test. The study revealed no significant differences between the transgenic tomato plants cv. Moneymaker and the wild type for important agronomic traits such as plant height, stem diameter, leaf area index, fruit weight, fruit weight per cluster, fruit weight per plant, fruit diameter, number of fruits per cluster, number of fruits per plant, and harvest index of miraculin. Some fruit quality traits such as fruit shelf-life, fruit hardness, total soluble solids, and content of glucose, sucrose, and fructose were equivalent to those of its counterpart, suggesting that miraculin transgene did not affect the expression of the observed traits. The miraculin transgenic tomato traits were more likely identical to those of wild-type except for the existence of the miraculin transgene. This will open the possibility for this special transgenic tomato to undergo further environmental safety assessment in the field test facility as a part of the biosafety assessment of genetically modified organism (GMO).